Environmental consciousness and green customer behavior: An examination of motivation crowding effect - Huang, Hao-Chen; Lin, Tzong-Huei; Lai, Mei-Chi; Lin, Tzu-Ling (International journal of hospitality management, 2014)
•This study validated the existence of the motivation crowding effect.•This study suggests a feasible environmental plan to respond to the motivation crowding effect.•The results show that environmental consciousness positively affects green consumer behavior.•Female and younger guests are more inclined to be environmentally friendly. The motivation crowding effect suggests that external money intervention weakens intrinsic motivation. The purpose of this study is to examine whether the motivation crowding effect occurs during the process where consumers try to be environmentally friendly. Thus, this study will first investigate the effect of environmental protection consciousness on green customer behavior, and then investigate the effect that incentive mechanisms have on environmental protection consciousness and green customer behavior. 458 hotel guests are used as research subjects. The results show that environmental protection consciousness positively affects green consumer behavior. Cash discount incentives have no effect on the choice of hotel guests to reuse their bed sheet or towels; on the contrary, environmental protective alternatives are great incentives for hotel guests to maintain environmentally friendly behavior. Regarding the demographics of hotels guests, female and younger guests are more inclined to be environmentally friendly. The contribution of this paper is proof of the existence of motivation crowding through an empirical analysis of hotel guests, which enlightens the hospitality industry on how to introduce environmentally friendly strategies in order to respond to motivation crowding.